INFLUENCE OF LONG-TERM THERAPY OF INHALATION GLUCOCORTICOSTEROIDS AND BRONCHIAL SPASMOLYTICS ON THE INDEXES OF RESPIRATORY FUNCTION AND HEART RATE VARIABILITY IN PATIENTS WITH BRONCHIAL ASTHMA WITH AN INITIALLY DIFFERENT VOLUMES OF THE FORCED EXPIRATORY VOLUME FOR 1 SECOND - PaskoЕ.N. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Aim of the study of long-term inhalation glucocorticosteroids and bronchial spasmolytics therapy influence on the RF and HRV indexes in patients with bronchial asthma (BA) with an initially different forced expiratory volumes for 1 second for development of proposals on the improvement of therapy and BA control. 140 patients (58 men and 82 women) with I-IV degreeof BA were examined in ambulatory terms. Mean age – 48±2,5 years. Duration of disease – 9,3±8,1 years. RF was estimated by computer spirograph «SpiroSom» XAI, were taken into account: respiration rate frequency (RRF), forced expiratory volume for 1st, 2nd and 3rd seconds (FEV1,2,3), momentary volume speeds of the forced exhalation in the moment of 25, 50, 75% MEFL (MVS25,50,75). For the heart rate variability (HRV) analysis computer electrocardiograph «Cardiolab+» XAI was used; heart rate in 1 minute (HR); total power of spectrum (TP); spectrum power in area of high and low-frequencies (LF, HF) and relation of low and high frequencies spectrum regions powers (LF/HF) were estimated. Results showed that long-term BA therapy has positive influence on the RF indexes (FEV1,2,3, MVS25,50,75) and HRV(ТР, LF,HF, LF) in all patients groups. The increase of the RF indexes depends on the initial FEV1 value and is most marked in the group of patients with FEV 1 values 80-60%. Interrelation between the FEV1 and HRV TP value in patients with BA confirms meaningfulness of regulatory mechanisms in breathing for state of health of patients and results of medical treatment.